Ultrastructure and histogenesis of the acral calcified angioleiomyoma. (2nd January 2016) - Díaz-Flores, Lucio; Gutiérrez, Ricardo; Alvarez-Argüelles, Hugo; González-Gómez, Miriam; García, Maria del Pino; Díaz-Flores, Lucio
ABSTRACT: We studied the ultrastructure, immunohistochemistry, and histogenesis of the acral calcified angioleiomyoma, observing three concentric zones: (a) pseudocapsular, thin, with spindle-shaped stromal cells (SCs), presenting scarce organelles and expressing CD34, (b) muscular, forming a ring, with smooth muscle cells of heterogenous phenotype (mainly in quantity and thickness of filaments, and in expression of h-caldesmon, αSMA, and desmin), and (c) central, extensive, calcified (spicular and/or star-shaped calcium deposits around collagen fibers), with pericytic involutive vasculature. The intratumoral vessels were thick (several layers of perivascular cells, with a continuum of phenotypes, resembling myopericytoma vessels) and thin (slit-like channels), without adventitial SCs or elastic material. The extratumoral vessels showed adventitial SCs (which contribute to form the tumor pseudocapsule), hyperplasia of the media and intima layers, and/or occlusion of the lumen by a wide, homogenous fibrotic central zone. Histogenetically, the collagenous matrix may act as a mineralization substrate and the calcifying modified pericytes as inductors; intratumoral vessels may originate from the peritumoral vessels or from the vessel where the tumor develops; and extratumoral vessel modifications, mimicking tumor features, concur with a minor repetitive trauma pathogenesis.